Time of day affects the tolerance distinction of sugarcane varieties to water deficiency through physiological traits - de Almeida Silva, Marcelo [UNESP]; Brunelli-Nascentes, Marcela Cristina [UNESP]; Santos, Hariane Luiz [UNESP]; Gonçalves Mendes, Carolina Ruv Lemes [UNESP]; de Almeida Prado Bortolheiro, Fernanda Pacheco [UNESP]; Fonseca Nascentes, Renan [UNESP]; Domingos Rodrigues, João [UNESP] (Taylor & Francis, 2023)
Water deficiency is one of the most limiting abiotic factors to sugarcane world production (Saccharum spp.). Data on chlorophyll content and gas exchange are used to select genotypes tolerant to water deficit. However, these variables are influenced by environmental factors, which vary intensely throughout the day. Thus, this research aimed to evaluate the influence of diurnal variation of gas exchange, leaf water potential, chlorophyll content, and SPAD index on the differentiation between genotypes tolerant and susceptible to water deficiency. The greenhouse experiment was conducted in a completely randomized 2 × 2 × 4 factorial scheme, with two varieties (RB867515/RB855453), two soil water tensions [without water deficiency (–D) and with water deficiency (+D)], and four evaluation times (7 am, 10 am, 1 pm, and 4 pm) with four replicates. RB867515 maintained greater CO2 assimilation, stomatal conductance, transpiration rate, intrinsic transpiration efficiency, leaf water potential, total chlorophyll content, and SPAD index under +D, regulating carbon gain about water loss and providing greater shoot biomass under +D compared to RB855453. The best times to perform the measurements for selecting tolerant genotypes based on physiological traits and specifically on the SPAD index are at 10 am and between 7 am and 10 am, respectively.
Keywords: chlorophyll content; drought tolerance; dry matter mass; gas exchange; Saccharum spp; SPAD index